Differentiating what is humorous from what is not. [article]. - Warren, Caleb
After 2.5 millennia of philosophical deliberation and psychological experimentation, most scholars have concluded that humor arises from incongruity. We highlight 2 limitations of incongruity theories of humor. First, incongruity is not consistently defined. The literature describes incongruity in at least 4 ways: surprise, juxtaposition, atypicality, and a violation. Second, regardless of definition, incongruity alone does not adequately differentiate humorous from nonhumorous experiences. We suggest revising incongruity theory by proposing that humor arises from a benign violation: something that threatens a person's well-being, identity, or normative belief structure but that simultaneously seems okay. Six studies, which use entertainment, consumer products, and social interaction as stimuli, reveal that the benign violation hypothesis better differentiates humorous from nonhumorous experiences than common conceptualizations of incongruity. A benign violation conceptualization of humor improves accuracy by reducing the likelihood that joyous, amazing, and tragic situations are inaccurately predicted to be humorous.-- (from the authors)